2013
DOI: 10.1016/j.jsc.2011.11.007
|View full text |Cite
|
Sign up to set email alerts
|

On symplectically rigid local systems of rank four and Calabi–Yau operators

Abstract: We classify all Sp 4 (C)-rigid, quasi-unipotent local systems and show that all of them have geometric origin. Furthermore, we investigate which of those having a maximal unipotent element are induced by fourth order Calabi-Yau operators. Via this approach, we reconstruct all known Calabi-Yau operators inducing a Sp 4 (C)-rigid monodromy tuple and obtain closed formulae for special solutions of them. (4, 8, 4) := Λ 2 L a+ 1 4 ⋆ H L 1 4 −a z 1 2 ⋆ H L b+ 3 4 ⋆ H L 3 4 −b z − 3 2 ⋆ H L 3 2 = 64 ϑ 4 + z −128 ϑ 4 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(34 citation statements)
references
References 16 publications
0
34
0
Order By: Relevance
“…, 1)) into the convolution of n + 1 local systems of rank one, each with a holomorphic solution of the type in Equation (3.5) with α = α i . This is a special case of a general classification result by Katz [51] that applies to every linearly rigid local system; see also [12]. In fact, Katz proved that every linearly rigid local system is obtained as tensor products and convolutions of rank-one local systems associated with the holomorphic solution (3.5).…”
Section: Convolution Formulasmentioning
confidence: 73%
See 2 more Smart Citations
“…, 1)) into the convolution of n + 1 local systems of rank one, each with a holomorphic solution of the type in Equation (3.5) with α = α i . This is a special case of a general classification result by Katz [51] that applies to every linearly rigid local system; see also [12]. In fact, Katz proved that every linearly rigid local system is obtained as tensor products and convolutions of rank-one local systems associated with the holomorphic solution (3.5).…”
Section: Convolution Formulasmentioning
confidence: 73%
“…We know that the elements of monodromy tuples induced by a rank-four Calabi-Yau operator must lie in Sp(4, C). Bogner and Reiter showed that all of the symplectically rigid monodromy tuples of quasi-unipotent elements admit a decomposition into a sequence of middle convolutions and tensor products of Kummer sheaves of rank one [12]. In particular, they are constructible using only tuples of rank-one.…”
Section: Summary Of Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[5, Section 2] and [2]. The following result is a consequence of the numerology of the middle convolution MC λ (cf.…”
Section: Middle Convolutionmentioning
confidence: 98%
“…Then we end up with a symplectically rigid triple in dimension 4 containing a bi-reflection. This arises from a monodromy triple of a hypergeometric differential equation of order 4 by taking the wedge product and applying a suitable middle convolution as shown in [2,Theorem 3.3]. Thus we are in the linearly rigid (hypergeometric) case.…”
Section: Introductionmentioning
confidence: 99%